2000
DOI: 10.1016/s0307-904x(00)00028-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost and probabilistic analysis of series systems with mixed standby components

Abstract: This paper deals with the reliability and availability characteristics of four different series system configurations with mixed standby (include cold standby and warm standby) components. The failure times of the primary and warm standby components are assumed to be exponentially distributed with parameters lambda and alpha, respectively. The repair time distribution of each server is also exponentially distributed with parameter mu. We derive the mean time-to-failure, MTTF, and the steady-state availability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…r cm NC C (6) where N is the expected number of failure per year and r C is cost of repair per failure.…”
Section: Expected Cost Of Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…r cm NC C (6) where N is the expected number of failure per year and r C is cost of repair per failure.…”
Section: Expected Cost Of Repairmentioning
confidence: 99%
“…The authors used semi-Markov method. The cost benefit analyses of system availability with warm standby units and imperfect coverage have been studied by [6][7][8][9][10]. Under the cost/benefit criterion, comparisons were made based on assumed numerical values given to the distribution parameters, as well as to the cost of the active and standby components.As noted from the literature, the redundancy of the system has been evaluated from performance and reliability perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In queueing and reliability literature, the notable research works on Markov modeling of machining system with standby support can be found [cf. Wang and Kuo (2000), Wang and Ke (2003), and Haque and Armstrong (2007)]. Shree et al (2015) proposed a Markov model for the machining systems with hot spares.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [5], [6] examined the cost analysis of two unit cold standby system involving preventive maintenance respectively. Reference [7] studied the cost and probabilistic analysis of series system with mixed standby components, and [8] studied cost benefit analysis of series systems with warm standby components involving general repair time where the server is not subject to breakdowns. The failure time and repair time are assumed to have exponential distribution.…”
Section: Introductionmentioning
confidence: 99%